Transformation of Education Management in Junior High School to Improve Learning Effectiveness Through the Application of Artificial Intelligence Technology - Supadi Supadi; Muhammad Najib; Nur Hamidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine the application of artificial intelligence technology in the transformation of education management in Junior High Schools to improve learning effectiveness. The research method used is a qualitative approach with a case study design, which involves observation, in-depth interviews with principals, teachers, and students, as well as analysis of documents related to the implementation of artificial intelligence-based digital learning. The data obtained was analyzed using thematic analysis techniques to identify the challenges, opportunities, and impacts of artificial intelligence technology in learning in junior high schools. The results of the study show that the application of artificial intelligence can increase the effectiveness of learning, especially in terms of personalization of learning and management of student learning time. The contribution of this research provides insight into the importance of artificial intelligence technology-based education management in improving the quality of learning at the junior high school level.